Institutional factors, entrepreneurship capital types, and economic growth in Asian countries - Dung Tien Luu (Universitas Islam Indonesia, 2020)
This paper investigates the relationship between institutional factors, entrepreneurial types, and economic growth. The analysis is based on an unbalanced panel data of 18 Asian countries over 2006-2018 using a 3SLS estimation method. It extends the neoclassical growth model with entrepreneurship capital types as an endogenous variable to the economic growth function. Findings/Originality: The results show that new business density and productive entrepreneurship significantly affect GDP per capita. Additionally, a reverse impact of economic growth on entrepreneurship is revealed. Institution's constructs, namely corruption control and the rule of law, are crucial to entrepreneurship, which in turn stimulate economic growth. The results also confirm the significant role of human capital, accumulating domestic investment, economic openness, and controlling inflation in the economic growth model of the Asian countries.